The Inactivation of JAK2/STAT3 Signaling and Desensitization of M1 mAChR in Minimal Hepatic Encephalopathy (MHE) and the Protection of Naringin Against MHE - Saidan Ding (Cellular Physiology and Biochemistry, 2014)
Background: We previously reported that elevation of intracranial dopamine (DA) levels from cirrhotic livers is implicated in the pathogenesis of minimal hepatic encephalopathy (MHE). Intracellular events in neurons, which lead to memory loss in MHE by elevated DA, however, remain elusive. Methods: In our present study, an MHE rat model, a DA - intracerebroventricularly (i.c.v.) injected rat model and DA-treated primary cortical neurons (PCNs) were used to study this issue using behavioral tests, double-labeled fluorescent staining, immunoblotting, and semi-quantitative RT-PCR. Results: Cognitive impairment was observed in MHE rats and DA (10 µg, i.c.v.)-treated rats. The levels of DA in the cerebral cortex of both MHE and DA (10 µg)-treated rats were increased. DA conversely modulated the p-JAK2/p-STAT3 levels in PCNs. In accordance, DA downregulated an anacetylcholine-producing enzyme, choline acetyltransferase (ChAT), and desensitized the M1-type muscarinic acetylcholine receptor (M1 mAChR). Furthermore, naringin completely restored cognitive function in MHE/DA (10 µg)-treated models by activating the JAK2/STAT3 axis, paralleling the upregulation of ChAT and sensitization of M1 mAChR. Conclusions: We propose a hypothesis accounting for memory impairment related to MHE: DA-dependent inactivation of the JAK2/STAT3 axis causes memory loss through cholinergic dysfunction. Our findings provide not only a novel pathological hallmark in MHE but also a novel target in MHE therapy.